Apraglutide, a novel once‐weekly glucagon‐like peptide‐2 analog, improves intestinal fluid and energy absorption in patients with short bowel syndrome: An open‐label phase 1 and 2 metabolic balance trial. Issue 7 (28th March 2022) - Eliasson, Johanna; Hvistendahl, Mark K.; Freund, Nanna; Bolognani, Federico; Meyer, Christian; Jeppesen, Palle B.
Abstract: Background: Apraglutide is a novel long‐acting glucagon‐like peptide‐2 (GLP‐2) analog designed for once‐weekly subcutaneous dosing, with the potential to increase fluid and nutrient absorption by the remnant intestine of patients who have short bowel syndrome (SBS) with intestinal insufficiency (SBS‐II) or intestinal failure (SBS‐IF). This trial investigated the safety and effects on intestinal absorption of apraglutide in patients with SBS‐II and SBS‐IF. Methods: In this open‐label, phase 1 and 2 trial, adult patients with SBS‐II ( n  = 4) or SBS‐IF ( n  = 4) and a fecal output of ≥1500 g/day received once‐weekly subcutaneous 5 mg apraglutide for 4 weeks. Safety was the primary end point. Secondary end points included change from baseline in intestinal absorption of wet weight (indicative of fluid absorption), electrolytes, and energy (by bomb calorimetry) measured by inpatient metabolic balance studies. Results: Common treatment‐related adverse events were decreased gastrointestinal (GI) stoma output ( n  = 6), stoma complications ( n  = 6), GI stoma complications ( n  = 5), nausea ( n  = 5), flatulence ( n  = 4), abnormal GI stoma output ( n  = 4), polyuria ( n  = 3), and abdominal pain ( n  = 3). The only treatment‐related serious adverse event (experienced in one patient) was abdominal pain. Apraglutide significantly increased wet weight and energy absorption by an adjusted mean of 741 g/day (95% CI, 194 to 1287; P  = 0.015) and 1095 kJ/day (95% CI, 196 to 1994; P  = 0.024), respectively. Sodium and potassium absorption significantly increased by an adjusted mean of 38 mmol/day (95% CI, 3 to 74; P  = 0.039) and 18 mmol/day (95% CI, 4 to 32; P  = 0.020), respectively. Conclusion: Once‐weekly 5 mg apraglutide was well tolerated in patients with SBS‐II and SBS‐IF and significantly improved the absorption of fluids, electrolytes, and energy.